Variasi Emisi Gas Nitrogen Dioksida saat Pembatasan Sosial Berskala Besar di Provinsi Jawa Barat dari Pengolahan Data Sentinel-5p - Anggraini, Tania Septi; Artaningh, Febzi; Sihotang, Elstri; Sakti, Anjar Dimara; Agustan, Agustan (Jurnal Penginderaan Jauh Indonesia, 2020)
Variations of Nitrogen Dioxide Emissions during Large Scale Social Restrictions in West Java Province from Sentinel-5P Satellite Data Processing Abstract. Sentinel-5P satellite that was launched in 2017 by ESA has a mission to monitor the earth’s atmosphere. One product of Sentinel-5P mission is the distribution of troposphere column density for several gases including nitrogen dioxide (NO2). NO2 emission is related to fossil fuel combustion from human activities such as factories and vehicle emissions. In 2020, COVID-19 is spreading all over the world including Indonesia. To break the chain of its distribution, therefore, the Indonesian Government enacts large scale social restriction (PSBB) in several areas including West Java Province. Sentinel-5P data was processed and analyzed to see the variations of changes in NO2 emission in several sampled cities in West Java. It is found that the NO2 emissions have decreased during PSBB. However, before Idul Fitri event on May 18, 2020, shows that the NO2 emission at Bandung Cities, Bandung District, and Bogor District increase significantly up to six-time higher. This activity also shows that daily information from Sentinel-5P satellite can be used for monitoring gases in the atmosphere.